ANALISIS KINERJA GURU MEMBANGUN PEMAHAMAN KONSEP, PENALARAN MATEMATIS, SERTA LITERASI TERHADAP HASIL BELAJAR SISWA - Purba, Ricky Rikardo; Sembiring, Thresia Yohana; Silangit, Menna Sri Ulina; Tambunan, Hardi; Pangaribuan, Firman (JURNAL CURERE, 2023)
The aim of this study is to test the direct influence of teacher performance in building student conceptual understanding of mathematical reasoning, as well as the direct impact of teacher's performance in constructing student's understanding of conceptual, mathematic reasoning and mathematics literacy on students' learning results. This study took the subjects of the students of the eighth grade in the 3rd grade state high school in Karo district of a total of 255 students. This research is a study of quantitative methods using ex-post facto approaches of a corrosional nature. Data is collected using tests, then processed and analyzed with path analysis techniques. The results of this study show that: (a) there is a direct influence of the teacher's performance in building conceptual understanding of the student's mathematical reasoning; (b) there has been a direct impact of the teachers' performance in constructing the students' understanding of conceptual reasoning and mathematics literacy on student learning outcomes.